Present conditions may mediate the legacy effect of past land‐use changes on species richness and composition of above‐ and below‐ground assemblages. (12th June 2017) - Janssen, Philippe; Bec, Stéphane; Fuhr, Marc; Taberlet, Pierre; Brun, Jean‐Jacques; Bouget, Christophe
Abstract: In forest ecosystems, the influence of landscape history on contemporary biodiversity patterns has been shown to provide a convenient framework to explain shifts in plant assemblages. However, very few studies have controlled for present human‐induced activities when analysing the effect of forest continuity on community structures. By cutting and removing trees, foresters substantially change stand ecological conditions, with consequences on biodiversity patterns. Disentangling the effect of past and present human activities on biodiversity is thus crucial for ecosystem management and conservation. We explored the response of plant and springtail species richness and composition to forest continuity (ancient vs. recent) in montane forests, while controlling for stand maturity (mature vs. overmature). We established 70 sites in landscapes dominated by unfragmented ancient forests where we surveyed plants and assessed springtails by analysing environmental DNA. Neither plant nor springtail species richness was influenced by forest continuity or by stand maturity. Instead, site‐specific characteristics, especially soil properties and canopy openness, were of major importance in shaping above‐ and below‐ground richness. For plant and springtail species composition, the effect of forest continuity was mediated by stand maturity. Thus, both plants and springtails showed a convergence in assemblage patterns with the increasing availability of overmature stand attributes. Moreover, soil and stand‐scale factors were evidently more important than landscape‐scale factors in shaping above‐ and below‐ground species composition. Synthesis . We clearly demonstrated that biodiversity patterns are more strongly influenced by present human‐induced activities than by past human‐induced activities. In the Northern Alps where our study sites were located, the colonization credit of most species has been paid off and the transient biodiversity deficit usually related to forest continuity has moved towards equilibrium. These findings emphasize the necessity to better control for local‐scale factors when analysing the response of biodiversity to forest continuity; we call for more research into the effects of forest continuity in unfragmented mountain forests. Abstract : We clearly demonstrated that biodiversity patterns are more strongly influenced by present human‐induced activities than by past human‐induced activities. In the Northern Alps where our study sites were located, the colonization credit of most species has been paid off and the transient biodiversity deficit usually related to forest continuity has moved towards equilibrium. These findings emphasize the necessity to better control for local‐scale factors when analysing the response of biodiversity to forest continuity; we call for more research into the effects of forest continuity in unfragmented mountain forests.